CURRENT PROBLEMS IN THE IMPLEMENTATION OF DIGITAL SERVICES IN SPORTS ORGANIZATIONS AND THEIR ANALYSIS - G‘ulamov Musurmon Sayfulla o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This study examines the introduction of digital services in sports organizations under the conditions of globalization and the digital economy. It highlights opportunities such as online ticketing, mobile applications, VR/AR technologies, digital marketing platforms, and data management systems, which improve transparency, efficiency, and fan engagement. At the same time, the research identifies key challenges including weak infrastructure, limited financial resources, insufficient digital literacy, organizational resistance, legal issues, and low-quality content. The findings suggest that effective implementation requires state support, private sector cooperation, strategic planning, and enhanced cybersecurity. Addressing these factors can significantly strengthen the competitiveness and sustainability of sports organizations in the global arena.